Unmet Need For Contraception Spatial Pattern In Muaro Jambi Regency, Jambi Province 2019-2021 - Lia Nurdini; Asparian; Muhammad Syukri; Sri Astuti Siregar (International Journal of Health Engineering and Technology, 2022)
Unmet Need for contraception is a key indicator to measure increased access to reproductive health and a key indicator to improve maternal and child health. In Indonesia, Unmet Need for contraception is the only strategic achievement of the BKKBN that has not been achieved and has an increasing trend from 2019 to 2021. Followed by an increase in unmet need for contraception for three consecutive years in Jambi Province with the highest number of unmet need for contraception in Muaro Regency. Jambi. This study aims to determine the spatial distribution pattern of the incidence of unmet need for contraception in Muaro Jambi Regency in 2019-2021. This research method is an epidemiological study using an ecological study design with a spatial approach. The sample in this study used an aggregate data analysis unit in 155 villages in Muaro Jambi Regency. This research was conducted from March to July 2022. Based on the results of spatial analysis, there is a tendency to increase the unmet need for contraception and there is a positive spatial autocorrelation between villages and there are 33 villages known as hot spot areas which are the main priority in overcoming the unmet need for contraception in Muaro Regency. Jambi.